Increased proportion of a CD38highIgD+ B cell subset in peripheral blood is associated with clinical and immunological features in patients with primary Sjögren's syndrome - Ishioka-Takei, Eriko (Clinical immunology (Orlando, Fla.), 2018)
Copyright © 2017 Elsevier Inc. All rights reserved.